Pilomatricoma mimicking ruptured epidermal cyst in a middle aged woman - Sudip Sarkar; Pranaya Kunal; Barnali Chowdhury; Kisalay Ghosh (Wolters Kluwer Medknow Publications, 2016)
Pilomatricoma is a benign tumor arising from the hair matrical cells. Most pilomatricomas appear in the first two decades of life as a solitary skin to a bluish colored nodule on head-neck area with an occasional sign of inflammation. Here, we present a case of pilomatricoma which appeared at 36 years of age with a history of recurrent inflammation and discharge mimicking ruptured epidermal cyst.